(untitled) (International journal of artificial intelligence, 2026)
This article examines mechanisms for managing foreign economic activity in Andijan region and identifies institutional and operational bottlenecks that constrain export growth and investment attraction. Using comparative institutional analysis, document review, and regional diagnostic reasoning, it systematizes management tools across regulatory, infrastructural, and service dimensions. Results propose an integrated mechanism model that improves coordination, risk management, and firm-level support.